A review of the genetics and epigenetics of central precocious puberty - Moise-Silverman, Joshua; Silverman, Lawrence A. (Frontiers in Endocrinology, 2022)
Gonadotrophin dependent sexual precocity, commonly referred to as central precocious puberty (CPP), results from a premature reactivation of the hypothalamic-pituitary-gonadal (HPG) axis before the normal age of pubertal onset. CPP is historically described as girls who enter puberty before the age of eight, and boys before the age of nine. Females are more likely to be diagnosed with idiopathic CPP; males diagnosed with CPP have a greater likelihood of a defined etiology. These etiologies may include underlying CNS congenital defects, tumors , trauma, or infections as well as environmental, genetic, and epigenetic factors. Recently, genetic variants and mutations which may cause CPP have been identified at both the levels of the hypothalamus and the pituitary. Single nucleotide polymorphisms (SNPs), monogenetic mutations, and modifications of the epigenome have been evaluated in relationship to the onset of puberty; these variants are thought to affect the development, structure and function of GnRH neurons which may lead to either precocious, delayed, or absent pubertal reactivation. This review will describe recent advances in the field of the genetic basis of puberty and provide a clinically relevant approach to better understand these varying etiologies of CPP